Zapolska’s Paris - Sobiecka, Anna (Porównania, 2024)
This article aims to reflect on the literary representations of Paris in Gabriela Zapolska's correspondance and published works. Her six year stay in Paris (from 1889 to 1895), described as a ‘Parisian university’ by Zbigniew Raszewski, was a period of development of the writer's acting and dramatic sensibilities (largely thanks to her collaboration with André Antoine in the Théâtre Libre), as well as the formation of her literary and artistic views, along with her budding conceptions of the city during this period. Analysing Zapolska's perception poetry and her shifting narrative perspective, we can observe the evolution of the topographic conception of the city in her descriptions of the nooks and crannies of urban space, which strongly metaphorise her experience of the city. Furthermore, in Zapolska's literary representations Paris becomes a seperate work of art, due to her fascination with modernity and with realising the new prospects that the modern city brings to the observer. The city of Paris, which is viewed as a living organism, is likened to a literary text, which is in turn likened to a cultural palimpsest. The process of aestheticising of urban space found in Zapolska's descriptions is proof of the literary shifts in viewing and experiencing the city at the turn of the 20th century – a passive observer becomes an active participant.